Oculoauriculofrontonasal Dysplasia Syndrome with Additional Clinical Features. (November 2017) - Tunc, Turan; Polat, Adem; Altan, Bilal; Yapici, Abdul Kerim; Saldir, Mehmet; Sari, Sabahattin; Sari, Erkan; Bayram, Yalcin; Eski, Muhitdin
Oculo-auriculo-vertebral spectrum and frontonasal dysplasia are two well-known examples of dysmorphology syndromes. Oculoauriculofrontonasal syndrome (OAFNS) is a clinical entity involving the characteristics of both OAVS and FND and is thought to be a result of the abnormal development of structures in the first and the second branchial arches, including the abnormal morphogenesis of maxillary processes. Herein we report a case of OAFNS with cliteral hypertrophy, premaxillary teeth, and inguinal hernia, features not previously reported in the literature.